Characterisation of Shigella species isolated from river catchments in the North West province of South Africa - Constance Wose Kinge; Moses Mbewe (South African Journal of Science)
The occurrence and distribution of Shigella species in water from the five river catchments in the North West province of South Africa were investigated. Shigella is a Gram-negative, non-motile, facultative anaerobic bacillus that causes shigellosis, an important cause of morbidity and mortality in high-risk populations (such as children, the elderly and immuno-compromised individuals) that depend on river water. A total of 54 water samples collected in winter (April 2007 to July 2007) and summer (December 2007 to March 2008) were cultured on Salmonella-Shigella agar by the spread-plate method. Suspected Shigella isolates obtained were characterised by primary biochemical (Triple Sugar Iron agar and agglutination) and molecular (polymerase chain reactions, PCR) tests. Amplification of the invasion plasmid gene (ipaH) by PCR was done to confirm the presence of Shigella spp. in water. In total, 214 Shigella boydii, 15 Shigella dysenteriae, 11 Shigella flexneri and 2 Shigella sonnei were confirmed by serotyping in both winter and summer samples. The ipaH gene (606 bp) was present in 176 and 49 of the winter and summer isolates, respectively. The presence of Shigella spp. in water was confirmed with over 90% specificity. The need for more effective management of these river catchments and the provision of potable water and sanitation facilities is needed to minimise the occurrence and transmission of water-borne diseases caused by these and other pathogenic bacteria.